2020
DOI: 10.1590/fst.05419
|View full text |Cite
|
Sign up to set email alerts
|

Screening and characterisation of gamma-aminobutyric acid (GABA) producing lactic acid bacteria isolated from Thai fermented fish (Plaa-som) in Nong Khai and its application in Thai fermented vegetables (Som-pak)

Abstract: This study aimed to evaluate the capability of lactic acid bacteria (LAB) isolated from different kinds of fermented fish products (Plaa-som) on the production of γ-aminobutyric acid (GABA). Among them, isolate L10-11, identified as Lactobacillus plantarum, offered the highest GABA production and was selected for further study. The highest production of GABA was obtained within 48h from the de Man, Rogosa and Sharpe (MRS) medium, having a pH range of 5-6. Oncreasing the monosodium glutamate (MSG) concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…In this study, the highest capacity of GABA-producing LAB, L. brevis F064A, was isolated from Thai fermented sausage ( Sai Krok Isan ). Previous reports have shown many GABA-producing LAB species from different sources such as Lactiplantibacillus plantarum L10-11 was isolated from plaa-som (Thai fermented fish) [ 36 ], Lactiplantibacillus pentosus SS6 was isolated from fermented mulberry fruit [ 37 ], Companilactobacillus futsaii CS3 was isolated from Thai fermented shrimp or Kung-Som [ 38 ], Latilactobacillus sakei A156 was isolated from Korean fermented seafood or Jeot-gal [ 39 ], three strains of L. brevis and one of Lactococcus lactis were isolated from Spanish cheese [ 40 ], five strains including Lactiplantibacillus plantarum, L. brevis , Leuconostoc mesenteroides , Leuconostoc lactis and Weissella viridescens were isolated from kimchi [ 19 ], Companilactobacillus farciminis D323 was isolated from a Myanmar traditional fermented fishery product [ 17 ], Lacticaseibacillus paracasei NFRI 7415 was isolated from Japanese traditional fermented fish or Funa-sushi [ 41 ]. In addition to fermented foods, GABA-producing LAB as L. plantarum Taj-Apis362 was isolated from honeybees [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the highest capacity of GABA-producing LAB, L. brevis F064A, was isolated from Thai fermented sausage ( Sai Krok Isan ). Previous reports have shown many GABA-producing LAB species from different sources such as Lactiplantibacillus plantarum L10-11 was isolated from plaa-som (Thai fermented fish) [ 36 ], Lactiplantibacillus pentosus SS6 was isolated from fermented mulberry fruit [ 37 ], Companilactobacillus futsaii CS3 was isolated from Thai fermented shrimp or Kung-Som [ 38 ], Latilactobacillus sakei A156 was isolated from Korean fermented seafood or Jeot-gal [ 39 ], three strains of L. brevis and one of Lactococcus lactis were isolated from Spanish cheese [ 40 ], five strains including Lactiplantibacillus plantarum, L. brevis , Leuconostoc mesenteroides , Leuconostoc lactis and Weissella viridescens were isolated from kimchi [ 19 ], Companilactobacillus farciminis D323 was isolated from a Myanmar traditional fermented fishery product [ 17 ], Lacticaseibacillus paracasei NFRI 7415 was isolated from Japanese traditional fermented fish or Funa-sushi [ 41 ]. In addition to fermented foods, GABA-producing LAB as L. plantarum Taj-Apis362 was isolated from honeybees [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A GABA-producing LAB strain of Lactobacillus plantarum L10-11 which was isolated from Thai fermented fish (Plaasom) in the fresh market at Nong Khai province, Thailand (Tanamool et al, 2020) was kindly obtained from Asst. Prof. Dr. Wichai Soemphol.…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%
“…), such as Lb. plantarum from cheese (Siragusa et al, 2007) and Thai fermented fish (Tanamool et al, 2020), Lc. lactis from kimchi and yoghurt (Lu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, fermented food samples containing GABA are used to screen for and isolate GABA-producing LAB, and it is not surprising that food samples with high GABA content may result in the isolation of promising strains showing good GABA-forming properties. Typical fermented foods used for isolating GABA-producing LAB are kimchi, where in one study 68 out of 230 LAB isolates showed the ability to convert glutamate to GABA [44] or other fermented vegetable, cheese [16] or fermented milk products, as well as various fermented meat or fish products including sausages, Thai fermented fish plaa-som [45], or traditional fermented Cambodian food, mainly based on fish, where 6 out of 68 LAB isolates showed a significant GABAproducing ability [1]. These screening / isolation strategies often resulted in the identification of strains capable of efficiently converting glutamate or in the discovery of novel, not-yet-identified producers of GABA, which show promise as starter cultures for various fermented foods enriched in GABA.…”
Section: Biodiversity Of Gaba-producing Lactic Acid Bacteriamentioning
confidence: 99%